2023
DOI: 10.1038/s41598-023-36848-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, ancestral ranges and reclassification of sand dollars

Abstract: Classification of the Class Echinoidea is under significant revision in light of emerging molecular phylogenetic evidence. In particular, the sister-group relationships within the superorder Luminacea (Echinoidea: Irregularia) have been considerably updated. However, the placement of many families remains largely unresolved due to a series of incongruent evidence obtained from morphological, paleontological, and genetic data for the majority of extant representatives. In this study, we investigated the phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 50 publications
(106 reference statements)
3
22
0
Order By: Relevance
“…5 ). The Astriclypeidae, a scutelliform taxon hypothesized to be sister to all other extant scutelliforms ( Lee et al, 2023 ) is not found in these regions ( Ghiold & Hoffman, 1986 ) and lacks Gregory’s diverticulum ( Ziegler et al, 2016 ). The oldest fossil records of scutelliform echinoids (Eoscutellidae and Protoscutellidae) occur in North America, and it has long been proposed that this clade originated there ( Stefanini, 1924 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 ). The Astriclypeidae, a scutelliform taxon hypothesized to be sister to all other extant scutelliforms ( Lee et al, 2023 ) is not found in these regions ( Ghiold & Hoffman, 1986 ) and lacks Gregory’s diverticulum ( Ziegler et al, 2016 ). The oldest fossil records of scutelliform echinoids (Eoscutellidae and Protoscutellidae) occur in North America, and it has long been proposed that this clade originated there ( Stefanini, 1924 ).…”
Section: Discussionmentioning
confidence: 99%
“…The distinctive group of echinoids known familiarly as sand dollars is globally distributed along tropical to temperate coasts, and the flattened morphology is adapted to sandy, shallow littoral waters exposed to wave and tidal current energy ( Smith, 1984 ). The sand dollars are divided into the Laganiformes and Scutelliformes, considered to be either sister ( Mongiardino Koch & Thompson, 2021 ; Mongiardino Koch et al, 2022 ) or polyphyletic ( Lee et al, 2023 ) clades. Scutelliformes are often considered to be “true” sand dollars ( Mongiardino Koch et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…We would like to re-emphasize our contribution on re-classification of Scutelliformes based on our new findings and appreciate the valid criticism raised by Koch 1 . In his reply to our work 2 , Koch 1 criticized the use of a dataset based on four molecular markers (two mitochondrial loci: Cox1 and 16S , and two nuclear ones: 28S and H3 ) for a reassessment of the classification of sand dollars. Koch 1 pointed out the incongruence of certain deeper level splits in the tree published in our recent work 2 with those based on their genome-scale datasets 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In his reply to our work 2 , Koch 1 criticized the use of a dataset based on four molecular markers (two mitochondrial loci: Cox1 and 16S , and two nuclear ones: 28S and H3 ) for a reassessment of the classification of sand dollars. Koch 1 pointed out the incongruence of certain deeper level splits in the tree published in our recent work 2 with those based on their genome-scale datasets 3 . One of the taxonomic disagreements is the position of Laganiformes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation